Affording accessibility for disabled children in the school built environments - Sjahrial, Emilda Rita; Abdul Rahim, Asiah (2008)
The objectives of this paper are first to introduce various concepts of accessibility that describe independence and easy mobility as derived from international theories. Secondly, to investigate the types of barriers which incur difficulties to people with disabilities such as the physically challenged children with diverse disabilities, including those who are wheelchair-bound, visually impaired, hearing impaired, or having multiple disabilities in the school built environments. Disabled children should have rights to accessible resources and facilities provided in schools. Finally, the study aims to analyse the range and suitability of the set-ups afforded for the disabled children at selected schools in corresponding to the requirements stipulated in the Uniform Building By-laws, Malaysian Standards Codes of Practice, as well as provisions in the recently gazetted Persons with Disabilities Act, 2007. The research methodology used includes table research, access audit, observations, plan analyses, checklist, and questionnaires. The data will be analysed based on both qualitative and quantitative approaches. The expected outcome of this paper is the added significance on the importance of access in school buildings and awareness on the standards for the disabled children in order to support and achieve the concepts of universal design.